Educational video games to improve the learning process - Alejandro Cachay-Gutierrez; Michael Cabanillas-Carbonell (Institute of Advanced Engineering and Science, 2024)
The pandemic has made us quickly migrate to virtual environments, for this reason, we must look for quality education mechanisms, thus continuing with the same level of traditional teaching. This research aims to determine the influence of an educational video game in improving the learning process, for which a study was carried out on first-cycle university students. The level of the research is explanatory, of the applied type, with a quantitative approach and quasi-experimental design. We worked with two groups already formed in which 65 students participated. The following results were obtained: an increase in the grade of motivation of 12.9%, an improvement in the acquired knowledge indicator of 46.34%, and an improvement in the obtained qualification indicator of 12.77%. Therefore, it is concluded that an educational video game influences the motivation, acquisition, and application of learning.